2020
DOI: 10.1038/s41564-019-0647-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective sequestration of signalling proteins in a membraneless organelle reinforces the spatial regulation of asymmetry in Caulobacter crescentus

Abstract: Selective recruitment and concentration of signaling proteins within membraneless compartments is a ubiquitous mechanism for subcellular organization 1 – 3 . The dynamic flow of molecules into and out of these compartments occurs on faster timescales than for membrane-enclosed organelles, presenting a possible mechanism to control spatial patterning within cells. Here, we combined single-molecule tracking and super-resolution microscopy, light-induced subce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 92 publications
6
131
0
Order By: Relevance
“…Fortunately, single-molecule tracking has recently emerged as a powerful tool for examining LLPS in vivo (51,111,112). Indeed, the strongest evidence for bacterial condensates to date comes from single-molecule tracking of proteins in polar microdomains in Caulobacter (113). This study revealed that PopZ imposes a diffusion barrier to cytosolic proteins and restricts the mobility of signaling molecules at the cell poles.…”
Section: Single-molecule Tracking As a Tool For Examining Llps In Vivomentioning
confidence: 99%
“…Fortunately, single-molecule tracking has recently emerged as a powerful tool for examining LLPS in vivo (51,111,112). Indeed, the strongest evidence for bacterial condensates to date comes from single-molecule tracking of proteins in polar microdomains in Caulobacter (113). This study revealed that PopZ imposes a diffusion barrier to cytosolic proteins and restricts the mobility of signaling molecules at the cell poles.…”
Section: Single-molecule Tracking As a Tool For Examining Llps In Vivomentioning
confidence: 99%
“…The liquid-like behavior of condensates has been tested by fluorescence recovery after photobleaching (FRAP) and by observing droplet fusion events (17,21,24,26,28). Finally, (18,21,26,30) and measured the diffusive properties of their molecular components (23,26,31,32). As the methods improve and rigorous controls are implemented, single-molecule methods are becoming increasingly critical for understanding bacterial subcellular organization due to the very small size of the relevant features in these microscopic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In C. crescentus, two hypotheses have been put forward to explain the condensation of CckA into a polar focus. First, CckA was shown to require a high enough local concentration to self-interact efficiently and become active as a kinase [26,27,77,78]. In addition, its Finally, there may be a pathway that acts in parallel to ChpT to transfer signals from CckA to CtrA (oval F, 29%).…”
Section: Plos Geneticsmentioning
confidence: 99%
“…accumulation at the flagellated pole may help to establish a gradient of CtrA~P with a maximum close to the pole-proximal replication origin, thereby blocking replication initiation in the (nascent) swarmer cell [77,79,80]. The absence of a polar CckA focus in the bud compartment of H. neptunium may suggest that CckA activity is not regulated at the level of protein concentration in this species, unless its activity is triggered at considerably lower threshold levels.…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation